Does genotypic diversity of Hydrocotyle vulgaris affect CO2 and CH4 fluxes? - Zhu, Jia-Tao; Xue, Wei; Gao, Jun-Qin; Li, Qian-Wei; Yu, Wen-Han; Yu, Fei-Hai (Frontiers in Plant Science, 2023)
Biodiversity plays important roles in ecosystem functions and genetic diversity is a key component of biodiversity. While effects of genetic diversity on ecosystem functions have been extensively documented, no study has tested how genetic diversity of plants influences greenhouse gas fluxes from plant-soil systems. We assembled experimental populations consisting of 1, 4 or 8 genotypes of the clonal plant Hydrocotyle vulgaris in microcosms, and measured fluxes of CO2 and CH4 from the microcosms. The fluxes of CO2 and CO2 equivalent from the microcosms with the 1-genotype populations of H. vulgaris were significantly lower than those with the 4- and 8-genotype populations, and such an effect increased significantly with increasing the growth period. The cumulative CO2 flux was significantly negatively related to the growth of the H. vulgaris populations. However, genotypic diversity did not significantly affect the flux of CH4. We conclude that genotypic diversity of plant populations can influence CO2 flux from plant-soil systems. The findings highlight the importance of genetic diversity in regulating greenhouse gas fluxes.